Histopathological Study on the Proposed Pathogenesis of Intratarsal Keratinous Cysts. Issue 4 (July 2019) - Tang, Tina; Brownstein, Seymour; Chen, Henry; Jordan, David R.; Iacob, Codrin E.; Blanco, Paula; Farmer, James
Abstract : Purpose: Intratarsal keratinous cysts (IKCs) are a recently described entity that is frequently misdiagnosed clinically as chalazia and mislabeled in the literature as "intratarsal epidermal inclusion cysts" or "epidermoid cysts." It is important to accurately diagnose IKCs and distinguish them from chalazia because IKCs require a complete surgical excision and can exhibit multiple recurrences following curettage. The authors performed a retrospective case series to further elucidate the pathogenesis of IKCs and to determine the diagnostically optimal panel of stains for diagnosis. Methods: A study group of 8 specimens of IKCs and control specimens of epidermal inclusion cysts were obtained from their pathology laboratories. The authors compared the histological and immunohistochemical profile of IKCs and epidermal inclusion cysts by staining sections from each specimen with hematoxylin and eosin, periodic acid-Schiff, Masson trichrome, cytokeratin 5, cytokeratin 17, carcinoembryonic antigen, and epithelial membrane antigen. The immunoreactivity data were then analyzed using a 2-tailed Mann-Whitney test, assuming a nonparametric population ( p < 0.05 is significant). Results: Histopathologically, IKCs are embedded in the tarsus lined by stratified squamous epithelium with an inner undulating cuticle filled with a compact keratinous-appearing material. The authors demonstrate that IKCs develop progressively from dilated meibomian ducts to the formation of complete cysts with their markers. The most valuable immunochemical stains to diagnose IKC were cytokeratin 17, carcinoembryonic antigen, and epithelial membrane antigen ( p < 0.05 with each). Conclusions: These findings provide a better understanding of the pathogenesis and the immunohistochemical findings of this relatively new entity allowing for more appropriate diagnosis of IKCs aiming to reduce future complications from their management. Abstract : Utilizing histochemical and immunohistochemical examinations, this study demonstrates that intratarsal keratinous cysts are most likely derived from the meibomian ducts and can best be characterized with 3 immunohistochemical stains, cytokeratin 17, carcinoembryonic antigen, and epithelial membrane antigen.